PEMBUATAN STICK DARI IKAN TONGKOL (Euthynnus Affinis) UNTUK PEMBERDAYAAN IBU RUMAH TANGGA DI DESA KUTA BLANG, KECAMATAN SAMADUA, KABUPATEN ACEH SELATAN - Absah Absah; Uswatun Hasanah (Marine Kreatif, 2022)
Tuna is the main Indonesian marine fishery commodity. Tuna meat has nutritional content and tastes that are liked by all people ans is a raw material for processed foods that are available throughout the year. This service activity aims to provide knowledge and skiils on how to make tuna sticks for hausewiives in kuta blang village. The service activity method uses the lecture method for knowledge transfer and technical guidance for direct practice. There are stages of this activity, namely the first stage (1), providing knowledge and theory about the handling of materials and processing tuna fish sticks, the second stage (2), namely giving practice directl to the village women of kuta blang how to process tuna sticks, and the third stage (3), namely training activities carried out through mentoring to women from the village of kuta blang regarding the packaging process after processing tuna into tuna stick products. Assistance is provided in producing tuna sticks both on a household scale and also for marketing. This training involved members of village development students who were accompanied by fish cadres white participanted in the activity from beginning to end and succeeded in making very good tuna fish sticks and have also been able to produce tuna fish sticks both for household scale and to be marketed.